Bridged bicyclic peptides: Structure and function. Issue 3 (9th March 2018) - Thombare, Varsha J.; Hutton, Craig A.
Abstract: Bicyclic peptides are conformationally rigid molecules that can bind with high affinity and specificity to their protein target, yet are significantly more protease stable than their linear or monocyclic counterparts. This emerging class of peptides has great potential for the development of novel peptide therapeutics and molecular probes. In this review, we highlight the structural complexity, synthesis/biosynthesis, and biological applications of bridged bicyclic peptides. Abstract :